The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1017/s0043887111000050
|View full text |Cite
|
Sign up to set email alerts
|

Can Islamists Become Moderates? Rethinking the Inclusion-Moderation Hypothesis

Abstract: Recent years have seen a surge of studies that examine the inclusion-moderation hypothesis with reference to political Islam: the idea that political groups and individuals may become more moderate as a result of their inclusion in pluralist political processes. Most of these interventions adopt one of three foci: (1) the behavioral moderation of groups; (2) the ideological moderation of groups; and (3) the ideological moderation of individuals. After a discussion of various definitions of moderate and radical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(119 citation statements)
references
References 60 publications
1
107
0
11
Order By: Relevance
“…Still, while liberals attempt to claim the mantel of 'moderation' away from their Islamist competitors, particularly in their dealings with the West, it is not obvious that they can in fact claim it away from conservatives who participate peacefully in the democratic process and show what Schwedler has called 'behavioural moderation'. 12 Complicating matters further, Marwan Muasher, former Jordanian foreign minister and Jordan's first ambassador to Israel, has suggested that Western states have identified Arab moderation with a single issue -a willingness to work constructively with the Israelis on the peace process. (One could say the say the same for security cooperation with the West.)…”
Section: Introductionmentioning
confidence: 99%
“…Still, while liberals attempt to claim the mantel of 'moderation' away from their Islamist competitors, particularly in their dealings with the West, it is not obvious that they can in fact claim it away from conservatives who participate peacefully in the democratic process and show what Schwedler has called 'behavioural moderation'. 12 Complicating matters further, Marwan Muasher, former Jordanian foreign minister and Jordan's first ambassador to Israel, has suggested that Western states have identified Arab moderation with a single issue -a willingness to work constructively with the Israelis on the peace process. (One could say the say the same for security cooperation with the West.)…”
Section: Introductionmentioning
confidence: 99%
“…More broadly, moderation is generally tied to liberal views of individual rights and democratic notions of tolerance, cooperation, and political pluralism (Schwedler, 2011). For instance, Somer refers to "moderation of political Islam through the embrace of democracy, modernity and liberal global economy" (2007: 1272).…”
Section: Theoretical Propositions Of Political Islammentioning
confidence: 99%
“…According to this view, religious radicals typically seek to replace the entire political system and eschew political pluralism (Schwedler, 2011). According to Hafez (2003), they tend to "reject accommodation with the state regime, refuse to participate in its institutions," and may "insist on the necessity of violent revolution or mass mobilization to Islamize society and politics" if necessary (6).…”
Section: Theoretical Propositions Of Political Islammentioning
confidence: 99%
“…Ashour (2007) reserves the term moderation to refer to ideological realignment toward democratic principles, and employs deradicalization to denote a rejection of violent methodologies (Ashour, 2007, p.599-600). Schwedler (2011) advocates adopting distinctive terms for specific issue areas.…”
Section: Moderationmentioning
confidence: 99%